The Impact of Customer Relationship Management Systems in Small Business Enterprises1. (November 2016) - Wynn, Martin; Turner, Phillip; Banik, Amitave; Duckworth, Gary
Abstract : The implementation of new customer systems can be a major challenge for small businesses, but they can deliver significant benefits when accompanied by appropriate staff upskilling and associated process improvements.